CLASSIFICATION OF TERMINOLOGTERMS IN DEVONU LUG'ATIT-TURK (ON THE BASIS OF REAL EXAMPLES) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
“Devonu lug'atit turk” contains more than 250 proverbs and sayings, dozens of poems. Another important aspect of this work is that the names of relatives and clans are given, how they are pronounced, the synonyms of these terms and their place of origin are proved on the basis of evidence. In addition, Devonu lug'atit-turk highlights the gender category of kinship.